Balancing Public and Private Value for the Digital Television Era - Evens, Tom; Verdegem, Pieter; De Marez, Lieven (Javnost-The Public, 2010)
As the digital switchover is the result of the dynamic interplay between economic, social and political interests, this article reflects on the role of all stakeholders involved in the switch to digital television services. It aims to discuss the trade-off between public and private policy interests focussing on strategies for preparing the transition process and the digital take-off as well as on future opportunities that become available in the spectrum (digital dividend). Based on a comparative study amongst three European countries, it is demonstrated that government has played an important role in the development of the digital television landscape in the past, and it is argued why policy makers should continue to do this in the future. Instead of a solely market-driven approach, a strong plea is made for a better understanding of stakeholders’ expectations in deploying public policies and business strategies concerning the digitised media landscape.